Pengenalan Integrasi Big Data Dalam Akuntansi Pemerintah Guna Peningkatan Akurasi Dan Kecepatan Pelaporan Keuangan Desa - Febrianto, Sucipto; Sinta, Dwi; Rini, Puspa; Oktari, Vivi; Novianti, Maya; Sitorus, Lizvan; Oktarina, Tika; Susanto, Edy (Jurnal Gotong Royong, 2024)
Technology's quick development has affected many industries, forcing them to adopt new technologies in order to stay up to date and adapt to changes. One industry that benefits greatly from the integration of technology is the banking sector. Village As public bodies in charge of overseeing state finances and resources, governments must place a high priority on accountability and transparency to guarantee the effective and efficient use of public monies. Fast and precise financial reporting has become essential, and in order to remain relevant, accounting firms have had to embrace and incorporate technology. In accounting, technology is essential. Systems that are integrated with information technology can improve accuracy and lower human error. Database systems, often known as Big Data, are one technological advancement that has a big influence on accounting procedures. The general public and village officials participated in this community service project, which was carried out in Sentral Baru Village. Village authorities struggle to adequately convey their financial management initiatives, and the community views the village government as dishonest in its handling of local funds. Thus, the goal of integrating technology into governmental financial management is to promote transparency and mutual trust by giving village officials and the community information and insights. An interactive lecture technique was employed for this community service project. Village leaders and the community consequently developed an awareness of financial management and its procedures.